A Standard Cost Application of Matrix Algebra. - Frank, Werner; Manes, Rene (The Accounting Review, 1967)
This article focuses on a study which illustrated the application of a matrix algebra formulation and solution to the problem of calculating standard prime cost variances. If the total material and labor price, mix, and quantity variances for all components are desired, these may be obtained by accumulating the relevant variances for all individual components. If there are a larger number of individual components involved in the manufacture of a single product, certain efficiencies in the computation of these variances may be achieved by setting up the basic data in matrix form and using simple matrix operations to perform the arithmetic. There are several advantages to be gained from the expression of accounting procedures, such as the calculation of standard cost variances, in mathematical form. In the first place, the explicit statement of the variables to be used in the analysis and the mathematical derivation of the formulas involved make it possible for the cost accountant to see clearly what the key elements in the analysis are and how the computational rules which an accountant later follows automatically were arrived at.